From a life of physics - Bethe, H.A (World Scientific, 1989)
A compilation of previously unpublished lectures delivered at the International Centre for Theoretical Physics by the pioneers and creators of modern physics --Bethe, Dirac, Heisenberg, Wigner, Klein and Landau (the sixth delivered by E Lifshitz). By sharing with us their own lives of physics, these outstanding physicists convey the sense of total dedication, the pleasure and elegance of scientific creation at its peak. Readers would acquire a deeper sense of the scope and nature of physics, and the insights of its fascinating diverse disciplines as the developments of modern physics are being unfolded through history